2015
DOI: 10.1016/j.polymer.2015.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the glass transition temperature at the atom-level in select model polyamides: A molecular dynamics study

Abstract: The molecular influence on glass transition temperature (T g ) of select model polyamides was investigated by atomistic modeling. These include nylon 6,6, nylon 6,12, a cycloaliphatic polyamide consisting of 4,4'-methylene-bis(cyclohexylamine) and dodecanedioic acid, as well as a corresponding aromatic counterpart consisting of 4,4'-methylenedianiline and dodecanedioic acid. For each model system, all-atom atomistic molecular dynamics simulations were used to discern and differentiate parameters such as free v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 50 publications
(47 reference statements)
0
30
0
Order By: Relevance
“…The short chains may result in end effects, while the long chains may be out of the calculation ability of the computer . Here a molecular chain with 50 repeating units, which is long enough to show the movements of segments, density and solubility parameter of NBR, was chosen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short chains may result in end effects, while the long chains may be out of the calculation ability of the computer . Here a molecular chain with 50 repeating units, which is long enough to show the movements of segments, density and solubility parameter of NBR, was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…In general, molecular simulation can be divided into molecular mechanics (MM), Monte Carlo (MC) methods, and molecular dynamics (MD) simulations . Mimicking real systems as much as possible, MD simulation is a powerful theoretical tool to understand the microstructure–property relationships . For example, Tanya et al .…”
Section: Introductionmentioning
confidence: 99%
“…In early 1990s, it was demonstrated that the Volume‐Temperature curves obtained from molecular dynamics (MD) simulations could be used to locate volumetric T g of simple polyolefin . Until now, this strategy has been extensively validated against many complex polymers, such as polycyanurates, polyamides, epoxy resins, etc. Furthermore, effects of various factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Diagrams of density versus temperature were used to calculate the glass transition temperatures and other thermal transitions. We found that second-degree polynomials better described the density between thermo-mechanical transitions rather than a linear correlation, the latter being the correlation most used in the literature, [36][37][38][39][40]19] the latter is true for the topology method where the correlation coefficient (R 2 ) was equal to 1.000.…”
Section: Discussionmentioning
confidence: 99%